Unveiling deixis expressions in the Oxford junior secondary English webinar by Icy Lee - Rifiyani, Andri Jamaul; Dzulfikri, Dzulfikri; Elfiyanto, Sonny (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The significance of deixis expression within the English language context, particularly within the spoken form, is crucial for the further examination of deixis as a specific area of pragmatics in order to enhance the theory and practice of verbal communication development. Thus, this recent investigation aimed to assess the presence of deixis in the Oxford junior secondary English webinar conducted by Icy Lee from a pragmatics and discourse analysis perspective. The researchers employed a qualitative research approach and adopted a descriptive analysis method. The data were acquired from a webinar video available on the YouTube channel and website of the Oxford junior secondary English webinar. The transcripts were meticulously analyzed and evaluated based on Levinson’s (1983) theory. In summary, the findings uncovered that Icy Lee’s webinar exhibited five classifications of deixis: person, time, social, discourse, and place deixis. Notably, person deixis was the most frequently utilized category, accounting for 223 utterances (48%). Each deictic expression possesses a diverse significance contingent upon the speech context. However, certain implications were still brought to light in this current investigation, and it is anticipated that subsequent researchers will explore the webinar in alternative contexts.